2019
DOI: 10.1002/jcp.28011
|View full text |Cite
|
Sign up to set email alerts
|

The Smad2/3/4 complex binds miR‐139 promoter to modulate TGFβ‐induced proliferation and activation of human Tenon's capsule fibroblasts through the Wnt pathway

Abstract: The activation and proliferation of human Tenon's fibroblasts (HTFs) play a vital role in the fibrosis in the pathology of the scar formation after the glaucoma filtration surgery. Transforming growth factor β1 (TGFβ1)/Smads signaling has been reported to promote fibrosis. In our previous study, we revealed that TGFβ1‐induced orbital fibroblast activation and proliferation through Wnt/β‐catenin signaling. As microRNA (miR)‐139 could target several factors in Wnt signaling to modulate fibrosis, here, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The TGF-β signaling pathway is multifunctional, and controls many biological functions related to development and diseases, usually via interactions with other important signaling pathways such as BMP, ERK, Hippo, JAK/STAT, Notch, NF-κB, MAPK, and Wnt signaling pathways 9,47,48 . In particular, crosstalk between the TGF-β and Wnt signaling pathways has been extensively studied 49,50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TGF-β signaling pathway is multifunctional, and controls many biological functions related to development and diseases, usually via interactions with other important signaling pathways such as BMP, ERK, Hippo, JAK/STAT, Notch, NF-κB, MAPK, and Wnt signaling pathways 9,47,48 . In particular, crosstalk between the TGF-β and Wnt signaling pathways has been extensively studied 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several components of the Wnt signaling pathway, including Wnt3A52, β-catenin 9,49 , Fzd1, Fzd2 57 , Dkk1, and Sfrp1 58 , as well as downstream targets such as c-Myc and Axin2 58,59 , are regulated by SMAD4. CTNNB1 (also known as β-catenin), for instance, is induced by SMAD4 in human Tenon's capsule fibroblasts; this factor is involved in the promotion of cell proliferation and activation by TGF-β signaling pathways 9 . Conversely, nuclear β-catenin and other signature genes of the Wnt signaling pathway are upregulated in epithelial tumors harboring Smad4-KO 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,20 This study found that these specific miRNA were found to be upregulated in OHT stage of PXF compared to glaucoma through common target being SMAD 2/3 and TGFR1 and TGFR2, which suggests these miRNAs regulate TGF in PXF differently via possible double feedback loops acting differently in different disease stages. 21,22 Since these miRNA regulate TGF/ECM interactions, EMT as well as autophagy related debris clearing directly, these can serve as therapeutic targets for reversing/preventing the fibrotic changes in the TM and possibly clear off the complex aggregates blocking the inter-trabecular spaces. We chose to focus on PBMC related signatures since TGF related signature controlling cell processes would logically be expected to be more active in cells in the peripheral blood than in serum as seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It may also function as a suppressor of HSC proliferation either through control of Rac1 or/and AKT1 10 , 19 . While there are as yet no reports of a specific function for the miR-139 class of microRNAs in HSC, miR-139-5p is observed to be downregulated in human non-alcoholic fatty liver disease (NAFLD) and primary billiary cholangitis (PBC) 20 and over-expression of miR-139 in primary human fibroblasts blocks the stimulatory actions of TGFβ 21 and inhibits epithelial-mesenchymal transition (EMT) 22 . Expression of miR150-5p was unchanged during initiation but instead was depressed in the perpetuation phase, this indicating it may exert negative control on functions of the myofibroblastic HSC.…”
Section: Discussion/conclusionmentioning
confidence: 99%